Self-assessed attitudes of adolescents towards learning - Goras-Postica, Viorica (Pedagogika Społeczna Nova, 2021)
The article presents the results of a pedagogical study, recently conducted on a group of over 8 thou- sand adolescents on the self-assessment of attitudes towards learning. As technologies have shifted many points of focus in addressing learning as an essential aspect of the educational process, the author intended to analyze the representations of adolescents from the knowledge and information century, administering an online questionnaire consisting of different types of questions. The results revealed diverse and mature perceptions, problems of teacher-student, student-student relations, of the institutional process of organization / culture of learning, but also of its results, as perceived by the main actors of the educational act.